Analisis Efisiensi Tenaga Kerja Menggunakan Metode Work Sampling Untuk Menentukan Jumlah Optimal Pekerja di PT. X - Setiawan, Setiawan; Athaya, Qornullail; Mushoffa, Marieska Mahjati; Izhar, Pradiajy; Firdaus, Muhammad Afdhal (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The excessive number of workers in the packing area of PT. X, which is not proportional to actual productivity levels, indicates inefficiencies in work processes. This study aims to analyze labor efficiency using the Work Sampling method to determine the optimal number of workers required to meet production targets. The methodology includes random observations of work activities over two days, productivity analysis, performance rating assessment using the Westinghouse system, and the calculation of allowances based on workplace environmental factors. The results show that the labor productivity rate reached 90.91%, with a performance rating of 1.4 and an allowance factor of 1.122. The standard time calculated per unit of product is 1.4202 minutes. Based on these findings, the optimal number of workers needed to achieve the production target is six, which is more efficient than the current number of eight to ten workers. This study provides practical recommendations for optimizing human resources to enhance operational efficiency in the company.